Pengaruh Technology Acceptance Model Terhadap Intention To Use Dengan Kinerja Sebagai Variabel Moderasi Dalam Menggunakan Sistem Informasi Akuntansi - Hantono Hantono; William Tjong; Jony Jony (Owner : Riset dan Jurnal Akuntansi, 2023)
A well-implemented accounting information system can generate reliable financial information for the company. The use of technology in accounting information systems in running a business should consider the usefulness and ease of its users so that the system becomes effective. The purpose of this study is to analyze the influence of Perceived Usefulness, Perceived Ease of Use, Attitude Towards Use Against Intention to Use with performance as Moderation Variables. Research was conducted on staff and employees within the company in Medan City. The number of research samples as many as 77 people selected by the nonprobability sampling method. Data collection is done by questionnaire through google form and library studies that support this research. The method used in this study is to use the Structural Equation Model (SEM) equation using partial least square (PLS) tool version 3.0. PLS consists of external relationships (outer model) and internal relationships (inner model), cross loading > 0.7, Composite Reliability, Convergent Validity, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Based on the results of the analysis found that perceived usefullness, attitude towards using, perceived usefullness proved to have no positive effect on intention to use, while perceived ease of use variables had a positive effect on intention to use, perceived usefullness and perceived Ease of use has no moderate effect on performance and intention to use relationships, and while attitude towards using has a moderate effect on performance and intention to use relationships.